(untitled) (European Journal of Formal Sciences and Engineering, 2019)
Treaty of Rome of 1957 and following treaties on amending the Treaty of Rome contain a number of basic principles on which the EU is founded. Among these principles, the most important ones related to the public procurement are: prevention of discrimination based on nationality, free movement of goods; right and freedom of establishment of a business; the right to provide services. Spending of public money in Kosovo pursuant to the Law on Procurement is found on the following principles: economization and efficiency; equal treatment and non-discrimination; transparency; value for money. The average of open procedure application in EU countries is 73 percent based on notices, whereas in Kosovo is 82.80 percent based on notices. In the end of 2014, Kosovo commenced the development of electronic procurement platform. This project takes place within the Public Sector Modernization Project. The importance of the electronic procurement is stated in the statement of European Commission: “Modernization and opening of procurement markets across borders – including through the electronic procurement expansion – are crucial for the competition in Europe and creating new opportunities for businesses in EU”. A good procurement system in Kosovo will have an impact on elimination of negative phenomena (corruption and bad management) in the management of public expenditures from spending agencies, as well as an impact on increase of budget saving. Key words: public expenditures, value for money, bad management, procurement, electronic procurement.